Cropping system rotation in combination with harvest weed seed control for wild oat (Avena fatua) management - Breanne D. Tidemann; K. Neil Harker; Robert H. Gulden; Greg Semach; Cindy Gampe; Larry Michielsen; Patty Reid; Elizabeth Sroka; Jennifer Zuidhof (Weed Technology, 2025)
Wild oat is a significant weed of cropping systems in the Canadian Prairies. Wild oat resistance to herbicides has increased interest in the use of nonchemical management strategies. Harvest weed seed control techniques such as impact mills or chaff collection have been of interest in Prairie crops, with wild oat identified as a key target. To evaluate the effects of crop rotation maturity, harvest management, and harvest weed seed control on wild oat, a study was conducted from 2016 to 2018 at four locations in the Canadian Prairies. Two-year crop rotations with either early, normal, or late-maturing crops were implemented before barley was seeded across all rotations in the final year. In addition, a second factor of harvest management (swathing or straight cut) was included in the study. Chaff collection was used in this study to quantify wild oat seeds that were targetable by harvest weed seed control techniques. The hypothesis was that earlier maturing crops would result in increased wild oat capture at harvest and, therefore, lower wild oat populations. Wild oat density and wild oat biomass were lowest in the early maturing rotations. In addition, wild oat exhibited lower biomass in swathed crops than straight-cut crops. Wild oat seedbank levels reflected a similar trend with the lowest densities occurring in early maturing rotation, then the normal maturity rotation, and the late maturing rotation, which had the highest seedbank densities. Wild oat densities increased in all crop rotations; however, only harvest weed seed control and crop rotation were implemented as control measures. Wild oat numbers in the chaff were not reflective of the earliness of harvest. Crop yields suggest that competitive winter wheat stands contributed to the success of the early maturing rotations compared to other treatments. Early maturing rotations resulted in reduced wild oat populations, likely through a combination of crop competitiveness and rotational diversity, and harvest weed seed control management effects from earlier maturing crops.